Bending of thin catheter by tempo-spatial division of ultrasound emission and evaluation of viscosity effect. (21st June 2018) - Ushimizu, Hidetaka; Suzuki, Toshiya; Mochizuki, Takashi; Masuda, Kohji
Abstract: We have already experimented on the bending of a thin catheter with acoustic radiation force. Considering future in vivo applications, it is necessary to develop a method of bending a catheter in an arbitrary direction to adopt a limited installation position of ultrasound transducers on a body surface. Therefore, using a two-dimensional array transducer (256 elements, 1 MHz), which realizes not only the spatial design but also the dynamic variation of an acoustic field, we realized the bending of a thin catheter by forming multiple focal points. However, since the acoustic energy is dispersed with the multiple focal points, it was difficult to obtain sufficient displacement. Therefore, we attempted to bend the thin catheter with tempo-spatial division emission of a single focal point. Also, we compared the effect of the medium of not only water but also viscous liquid, which has similar viscosity to blood, where the bending performance of the catheter in the viscous liquid was reduced compared with that in water. Then, we derived the appropriate condition to bend the catheter with the transition rate of the focal point of 2.0 mm/s, and the spatial interval between 0.2 and 1.0 mm through various experimental trials. Finally, we succeeded in holding the tip of the catheter with the maximum displacement.